2013
DOI: 10.3109/14992027.2013.820000
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation for a child with cochlear nerve deficiency: Parental perspectives explored through narrative

Abstract: Findings highlight the central place of parental needs and perspectives in decision-making regarding a CI, particularly in the context of uncertain outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Respondents in the quantitative studies ranged from 19 (Steinberg et al, 2000) to 247 parents (Hyde, Punch, & Komesaroff, 2010). Qualitative studies ranged from case-study interviews with the parents of a single child (Kotjan, Purves, & Small, 2013) to interviews with 216 parents (Sach & Whynes, 2005). Only one study examined parental decision-making for a child with a unilateral hearing loss, involving 23 caregivers of children with unilateral aural atresia (Graham, Haworth, Chorney, Bance, & Hong, 2015).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Respondents in the quantitative studies ranged from 19 (Steinberg et al, 2000) to 247 parents (Hyde, Punch, & Komesaroff, 2010). Qualitative studies ranged from case-study interviews with the parents of a single child (Kotjan, Purves, & Small, 2013) to interviews with 216 parents (Sach & Whynes, 2005). Only one study examined parental decision-making for a child with a unilateral hearing loss, involving 23 caregivers of children with unilateral aural atresia (Graham, Haworth, Chorney, Bance, & Hong, 2015).…”
Section: Participantsmentioning
confidence: 99%
“…Parents were not always clear about their available options (Steinberg et al, 2003;Johnston et al, 2008;Mulla et al, 2013;Merugumala et al, 2017) or they felt that their only option was CI (Sach & Whynes, 2005;Hyde et al, 2010). Several papers indicated that families felt they had sufficient information to make the focal decision (Fitzpatrick et al, 2011;Incesulu et al, 2003;Johnston et al, 2008;Penaranda et al, 2011); however, others indicated that the parents felt they needed, or sourced, additional information (Alkhamra, 2015;Chang, 2017;Crowe, Fordham, et al, 2014;Decker et al, 2012;Fitzpatrick et al, 2011;Guiberson, 2013;Hardonk et al, 2010;Kluwin & Stewart, 2000;Hardonk et al, 2010;Kotjan et al, 2013;Steinberg et al, 2003). Other studies indicated that information was not balanced, or that there was conflicting advice on the best approach from professionals, which complicated their decision-making (Bruin & Nevøy, 2014;Eleweke & Rodda, 2000;Jackson et al, 2008;Kotjan et al, 2013;Matthijs et al, 2017;Mulla et al, 2013;Nelson, Herde, Munoz, White, & Page, 2017;Stroebel & Swanepoel, 2014;Uus et al, 2015;Wheeler et al, 2009).…”
Section: Knowledgementioning
confidence: 99%
See 1 more Smart Citation